Implementação de uma arquitetura experimental de aviônica modular integrada distribuída - Tamanaka, Gustavo Teruo Bernardino (Universidade Federal de São Carlos, 2017)
This work discusses the theoretical and experimental aspects for the implementation of Integrated Modular Distributed avionics. The distributed avionics technology is, still, a recent subject, but of great importance for the aeronautical industry, therefore this work tries to add information and to promote the discussion on the theme. To this end, this work sought to align theory and practice when developing an experimental bench in a simplified way. For the development of the bench, rapid prototyping circuits were used in order to simulate the commercial equivalents. The development of the bench took place as expected, resulting in a system capable of properly receiving the reading, the capture of sensors and the movement of actuators. In this way it is concluded that the proposed objectives were reached.
Implementation of an integrated distributed modular avionics experimental architecture
Keywords: DIMA; Aviônica; RTOS; ENGENHARIAS::ENGENHARIA MECANICA::PROJETOS DE MAQUINAS